2007
DOI: 10.1016/j.neuron.2007.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Two Families of TARP Isoforms that Have Distinct Effects on the Kinetic Properties of AMPA Receptors and Synaptic Currents

Abstract: Transmembrane AMPA receptor regulatory proteins (TARPs) are auxiliary AMPA receptor subunits that regulate both the trafficking and gating properties of AMPA receptors, and different TARP isoforms display distinct expression patterns in brain. Here, we compared the effects of four TARP isoforms on the kinetics of AMPA receptor currents. Each isoform slowed the deactivation of GluR1 currents, but the slowing was greatest with gamma-4 and gamma-8. Isoform-specific differences in desensitization were also observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
230
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(257 citation statements)
references
References 51 publications
19
230
1
1
Order By: Relevance
“…We next extended our analysis of colocalization and immobilization to other TARPs that are known to interact with and modulate the functions of AMPA-Rs (17,19,20,33). We chose γ-3, γ-4, and γ-8, which are functionally similar to γ-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next extended our analysis of colocalization and immobilization to other TARPs that are known to interact with and modulate the functions of AMPA-Rs (17,19,20,33). We chose γ-3, γ-4, and γ-8, which are functionally similar to γ-2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that TARPs directly interact with AMPA-Rs (11,13,27) and regulate both their localization and gating (14)(15)(16)(17)(18)(19)(20)22). The stoichiometry of TARP/AMPA-R complexes was recently deduced indirectly from functional population assays to be a maximum of four TARPs per AMPA-R complex (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, KA2 acts as an accessory subunit that controls in concert both the functional properties of KARs and their expression at the membrane surface (Pinheiro and Mulle, 2006), similarly to transmembrane-associated proteins TARPs for AMPA receptors (Cho et al, 2007;Milstein et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The micropipette tips were custom-made using filamented borosilicate glass capillaries (BF150-86-10, Sutter Instruments). sEPSCs and sIPSCs were recorded as described previously (50,51), with detailed settings described in SI Appendix, Fig. S1.…”
Section: Methodsmentioning
confidence: 99%